2021
DOI: 10.1002/capr.12437
|View full text |Cite
|
Sign up to set email alerts
|

Understanding suicidality and reasons for living amongst Doctoral Researchers: A thematic analysis of qualitative U‐DOC survey data

Abstract: Evidence regarding the mental health of Doctoral Researchers (DRs) is very limited; that which exists suggests DRs are particularly vulnerable to experiencing mental health difficulties during their PhD.Despite the associated jeopardy, however, to our knowledge there are no data published nor in the grey literature, reporting on suicidality amongst DRs. Using an online survey, we invited UK DRs to complete the Suicide Behaviour Questionnaire -Revised and qualitatively describe their experience of suicidality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Articles in this special section provide a step towards achieving these goals. These articles shed light on the needs of students who are typically under-represented when it comes to designing institutional policies and services, including the following: (1) the first study to explore suicidality in doctorate researchers and identify risk and protective factors against student suicidality (Hazell et al, 2021); (2) an archival study using practice-based data to gain insight into the risk factors associated with treatment-seeking students with pregnancy-related concerns (Markin et al, 2021); and (3) an interview study exploring the determinants of psychotherapy outcome expectations for students experiencing social anxiety and shedding light on students' willingness to engage with mental health interventions (Morrison et al, 2021).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Articles in this special section provide a step towards achieving these goals. These articles shed light on the needs of students who are typically under-represented when it comes to designing institutional policies and services, including the following: (1) the first study to explore suicidality in doctorate researchers and identify risk and protective factors against student suicidality (Hazell et al, 2021); (2) an archival study using practice-based data to gain insight into the risk factors associated with treatment-seeking students with pregnancy-related concerns (Markin et al, 2021); and (3) an interview study exploring the determinants of psychotherapy outcome expectations for students experiencing social anxiety and shedding light on students' willingness to engage with mental health interventions (Morrison et al, 2021).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…The questions that are asked within the scales measuring psychological distress, anxiety, or suicidal thoughts may prime participants' further responses to focus on adverse psychological experiences. Likewise, with interviews and focus groups, recruitment advertisements that mention mental health and wellbeing may elicit discussions of poor mental health and suicidal behaviour [49]. Using more neutral terminology within recruitment posters, participant information, and survey wording may be a way to negate this priming bias.…”
Section: Discussionmentioning
confidence: 99%
“…In their analysis of suicidal ideation within the U-DOC cohort, Hazell et al [49] revealed a reticence to discuss suicidal thoughts within universities, despite the quantitative findings indicating that 20-35% of doctoral students may be at risk of suicide. However, the researchers identify how self-selection bias may contribute to an overestimation of psychological distress in this sample [21].…”
Section: Academic Culturementioning
confidence: 99%
“…One involves how supervisees portray doctoral research in the context of the intense pressure they often face. Other research has highlighted how doctoral research students are at greater risk of experiencing mental health issues compared to the general population (Hazell et al, 2021; Metcalfe et al, 2018; Thorley 2017), which makes this an important area for further research. Another urgent issue to attend to is diversity in both research and research supervision, viewed from both the perspective of the supervisee and the supervisor.…”
Section: Discussionmentioning
confidence: 99%
“…Thorley (2017) and McPherson, Punch and Graham (2017) refer to how the transition to postgraduate research is often accompanied by disorientation, self-doubt and anxiety, and they suggest research supervision plays a key role here. Hazell et al (2021Hazell et al ( , 2020 add an alarming background to the need for more attention to student mental health and support. Using an online survey, Hazell et al (2020) invited UKbased doctoral researchers (DRs) to complete the Suicide Behaviour Questionnaire-Revised and qualitatively describe their experience of suicidality and its association with their PhD studies.…”
Section: Literature Reviewmentioning
confidence: 99%